CFD study of heat and mass transfer and entropy generation in a 3D solar distiller heated by an internal column - Al-Rashed, Abdullah A. A. A.; Öztop, Hakan Fehmi; Kolsi, Lioua; Boudjemline, Attia; Almeshaal, Mohammed A.; Ali, Mohamed E.; Chamkhag, Ali (Pergamon-Elsevier Science Ltd, 2019)
Three-dimensional computational analysis was performed to investigate the double diffusive natural convection inside a cubical solar distiller heated by a square-shaped column. Governing equations were developed using the 3D vector potential-vorticity and solved using the finite volume method. Different governing parameters, i.e., Rayleigh number 10(3) <= Ra <= 10(5), buoyancies ratio -10 <= N <= 10, geometrical parameter 0.1 <= L-h <= 0.7 for Le = 0.85 and Pr = 0.7 corresponding to humid air, were tested. It was found that both heat and mass transfer are strongly affected by the change of buoyancy ratio, geometrical parameter and Rayleigh number.
Keywords: Double diffusion; CFD; Complex flow structure; Vector potential-vorticity formalism; 3D solar distiller